Fraud in the Disposal or Encumbrance of Assets of the Conjugal Society - Rojas Ulloa, Milushka Felícitas (2015)
The subject matter of study whose main source of motivation fraud in the disposition or encumbrance of conjugal society. The provision for a spouse of property acquired in joint property is no problem, it is clear that for this you must have a special power.However, when the record is made with the DNI, where he or the spouse listed as single, then find a fact at odds with the good faith, i.e. an asset is recorded as its own, i.e. as single, when in fact acquired social good within marriage. In that sense, it is important to determine whether fraud disposition or encumbrance of assets of the conjugal partnership, without special power of the other is a legal void, voidable or unenforceable.